A comparison of owner perceived and measured body condition, feeding and exercise in sport and pet dogs - Kluess, Heidi A.; Jones, Rebecca L. (Frontiers in Veterinary Science, 2023)
Dog obesity is a significant problem in the US and elsewhere. The purpose was to evaluate factors contributing to pet obesity in sport and pet dog owners. Owners were recruited over social media to answer a questionnaire regarding demographics, health, body condition, feeding, exercise and dog related expenses. Owners identified as pet or sport dog owners. We asked owners to measure the pelvic circumference and hock to stifle length in their dogs in order to calculate percent fat. Owners reported that their dogs were in “ideal” body condition. However, percent fat calculated from owner measurements was significantly different between groups (Sport: 16±10%fat; Pet: 24±10% fat; p<0.05) and revealed that over 50% of the dogs were over fat. Owners reported feeding dogs a range of 413 to 1133 Kilocalories (Kcal) per day that correlated well with dog size (R=0.58; p<0.05). The size of the treats fed was smaller in the Sport dogs (treat was pinky nail to thumbnail sized) than in Pet dogs (treat was bigger than thumb to larger than palm). Owners reported walking their dogs on leash every day for 15-45 minutes per session. Overall, owners did a poor job in identifying correct body condition of their dogs. This is concerning because 50% of the dogs were over fat. Better understanding of correct body condition and feeding for the level of physical activity is still a critical issue in controlling obesity in pet dogs.